Technical Support for Maintaining Solar Power Plants in Plantation Areas, Sajen Village, Mojokerto - Widagdo, Reza Sarwo; Ardianik, Ardianik; Imam Suri Tauladan,; Slamet, Puji; Andriawan, Aris Heri; Hariadi, Balok (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Sajen Village is predominantly an agricultural and livestock-based community. However, the lack of sufficient electricity poses a significant challenge to the development of these sectors. Solar Power Generation Technology offers a sustainable solution due to the village’s potential for utilizing solar energy. To ensure the successful implementation of solar power plant, it is essential to provide the local community with adequate knowledge and skills in its operation, maintenance, and care. This community service program aims to introduce solar power plant to the residents of Sajen Village while equipping them with the necessary technical expertise. The program consists of several key activities: training on solar power plant operation and maintenance, an introduction to the principles of solar power plant design and installation, and evaluation sessions to assess the community's understanding. These activities are designed to empower participants to independently operate and maintain solar power plant systems. The final stage involves evaluating the program’s effectiveness by measuring the participants’ comprehension of solar power plant concepts, operations, and maintenance techniques. This initiative is expected to enhance the sustainability of Sajen Village's agricultural and livestock sectors by addressing the electricity shortage through renewable energy solutions. It also promotes community independence in managing solar power systems for long-term benefits